UPAYA PENINGKATAN ASPEK KOGNITIF MENGENAL WARNA MELALUI METODE EKSPERIMEN PENCAMPURAN WARNA PADA ANAK USIA 4-5 TAHUN DI TK PERTIWI FLAMBOYAN MINTOBASUKI - Farikhatun Nikmah; Titi Chandrawati (Smart Education, 2026)
This study aims to see the positive impact of the color mixing experiment method on improving cognitive aspects in early childhood. The problem that occurs is that children aged 4-5 years (Grade A) of Pertiwi Flamboyan Mintobasuki Pati Kindergarten still have difficulty in naming the colors resulting from mixing two types of colors. Classroom Action Research is carried out in two cycles. The subjects in this study were 9 children in the 4-5 year age group of Class A of Pertiwi Flamboyan Mintobasuki Pati Kindergarten in the 2025/2026 Academic Year. From this study, it shows that the experimental method of mixing colors can effectively improve children's ability to recognize colors. In addition, it turns out that the experimental method of mixing colors can also stimulate curiosity, creativity, and critical thinking skills in children. The percentage of the ability to recognize colors with a BSB assessment (very well developed) in the initial conditions (pre-cycle) was 11% or as many as 1 child, then in cycle I the percentage increased to 26% or as many as 2 children. And activities in cycle II the percentage of increased development of cognitive aspects of color mixing increased to 81.7% or as many as 8 children who obtained very well-developed results (BSB) and were able to achieve the predetermined indicators.